The relationship of emotional intelligence and knowledge sharing among non-academic staffs at UiTM Kampus Samarahan / Mohd Nazrin Shah Setriah - Setriah, Mohd Nazrin Shah; Stalia, Sylvia Dora (2017)
This chapter focuses on the background of the study on importance of emotional intelligence (El) in affecting knowledge sharing (KS). This study conducted among non-academic staff in LliTM Kampus Samarahan from various departments. Under this study there are sections that discusses on the background of study, identifying the problems statements regarding to this study which focusing on the gap between each of the objectives, research objective and then the explanation on information regarding to the scope of study. Another section is explaining on the significance of this study and finally there is section on the definition of terms that will be used on overall of the study.